New types of steel-FRP composite bar with round steel bar inner core: Mechanical properties and bonding performances in concrete. (10th May 2020) - Zhao, Debo; Pan, Jun; Zhou, Yingwu; Sui, Lili; Ye, Zenghui
Highlights: Production techniques of SFCB with round steel bar inner core were explored. SFCBs with round bar inner core have comparable tensile performances with SFCBs with ribbed bar inner core. The newly-developed SFCBs had bond strengths between round and ribbed rebars. Abstract: A steel-FRP composite bar (SFCB) combines the advantages of both fiber-reinforced polymer (FRP) and steel rebars. This paper introduces production techniques of the newly-developed SFCB with a round steel bar inner core. Then, based on the factory-produced SFCB, the mechanical properties of SFCBs under tensile tests are evaluated, and the bonding performances of SFCBs in concrete are tested and analyzed. The experimental and analytical results indicate that the tensile performances of these new types of SFCBs with a round bar inner core compare favorably with those of SFCBs containing a ribbed bar inner core. The SFCBs had bond strengths between round and ribbed rebars, and the rebar diameter and surface treatment are key factors influencing the bond strength of SFCB-concrete interface. Besides, the bond-slip behavior of SFCB-concrete specimens can be predicted by improving the bonding models of FRP bars.